On the coordination chemistry of triazolyl-substituted diborane ligands, prepared by 1,3-dipolar cycloaddition reactions between diazido-diboranes and alkynes - Vogler, Daniel; Schenker, Maurice; Ng, Kim Hao; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2023)
Metal-free cycloaddition reactions between a diazido-diborane and alkynes are used to synthesize new ditriazolyl-diborane molecules, a bis(ferrocenyl-1,2,3-triazolyl)-diborane and a bis(2-pyridyl-1,2,3-triazolyl)-diborane. Then, the bis(2-pyridyl-1,2,3-triazolyl)-diborane was used as polydentate ligand for the synthesis of larger architectures. Reaction with ditriflato-diborane yielded a tetracationic hexaboron compound, and reaction with metal salts yielded dicationic ring compounds with two hexacoordinate metal atoms and two integrated diborane units.
Gesehen am 21.12.2023